2022
DOI: 10.3389/fimmu.2022.902093
|View full text |Cite
|
Sign up to set email alerts
|

Biological Characteristics of HLA-G and Its Role in Solid Organ Transplantation

Abstract: Organ transplantation is a lifesaving option for patients with advanced diseases. Rejection is regarded as one of the most severe risk factors post-transplantation. A molecule that contributes to immune tolerance and resisting rejection is human leukocyte antigen (HLA)-G, which belongs to the non-classical major histocompatibility complex class (MHC) I family. HLA-G was originally found to play a role during pregnancy to maintain immune tolerance between mother and child. It is expressed in the placenta and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 139 publications
0
9
0
Order By: Relevance
“…Even though HLA-G by itself does not account for all the immunomodulation properties of EVTs, as demonstrated by Tilburgs et al [19], in vitro experiments with HLA-G transfects have demonstrated its immunomodulation effects [32][33][34][35]. This is further supported by the observation that aberrant HLA-G presence after organ transplantation is associated with a greater chance of graft acceptance [36]. This reinforces that EVTs are highly specialized cells.…”
Section: Discussionmentioning
confidence: 94%
“…Even though HLA-G by itself does not account for all the immunomodulation properties of EVTs, as demonstrated by Tilburgs et al [19], in vitro experiments with HLA-G transfects have demonstrated its immunomodulation effects [32][33][34][35]. This is further supported by the observation that aberrant HLA-G presence after organ transplantation is associated with a greater chance of graft acceptance [36]. This reinforces that EVTs are highly specialized cells.…”
Section: Discussionmentioning
confidence: 94%
“…Taking in to consideration the literature and our results lot of non‐unanimity is associated with regard to levels of sHLA‐G during various gestational stages and pregnancy complications. In general, increased expression of HLA‐G may reflect an attempt to control the immune derangement 73 . In order to use sHLA‐G as immunological tracer for successful pregnancy longitudinal studies are required tracking sHLA‐G levels from initial to final stages of gestation in association with the outcome of pregnancy (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…In general, increased expression of HLA-G may reflect an attempt to control the immune derangement. 73 In order to use sHLA-G as immunological tracer for successful pregnancy longitudinal studies are required tracking sHLA-G levels from initial to final stages of gestation in association with the outcome of pregnancy (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, numerous studies have been conducted to correlate HLA‐G haplotypes with disease susceptibility/morbidity utilized as a therapy predictor or in transplantation outcome (Amodio & Gregori, 2020). HLA‐G has tolerogenic properties that can help improve the survival rate of the allograft (Liu et al., 2022). Moreover, in 474 pregnancies, HLA‐G protein was found to be associated with a successful pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…HLA-G has tolerogenic properties that can help improve the survival rate of the allograft (Liu et al, 2022). Moreover, in 474 pregnancies, HLA-G protein was found to be associated with a successful pregnancy.…”
Section: Discussionmentioning
confidence: 99%